-11+3x+4=17

Simple and best practice solution for -11+3x+4=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11+3x+4=17 equation:


Simplifying
-11 + 3x + 4 = 17

Reorder the terms:
-11 + 4 + 3x = 17

Combine like terms: -11 + 4 = -7
-7 + 3x = 17

Solving
-7 + 3x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3x = 17 + 7

Combine like terms: -7 + 7 = 0
0 + 3x = 17 + 7
3x = 17 + 7

Combine like terms: 17 + 7 = 24
3x = 24

Divide each side by '3'.
x = 8

Simplifying
x = 8

See similar equations:

| -7x-8y=12 | | 0=-4 | | 4-4b=8(8+2b) | | x^2-(4p+1)x+(5p^2+2p)=0 | | y=296+7x | | y=7x+296 | | 3(w-2)+7=1-3w | | 4+v=3v-8 | | X=2(0) | | (-5)-(-2)=g+4 | | -60=6x-5y | | 34:4= | | -3(12-6x)=7(8-2x) | | (-35)=c+(-18) | | 5x+13=3x-93 | | X=2-2 | | $45.00-30%= | | -3(m-7)=2m-4 | | 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 |

Equations solver categories